RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN SISWA DAN PEMBAYARAN SPP BERBASIS WEB MENGGUNAKAN METODE WATERFALL (Studi Kasus : Madrasah Ibtidaiyah Raudlatul Anwar Pagedangan) - Anisa Indriyasari; Ardianto Moenir (CV. Multi Kreasi Media, 2022)
Madrasah Ibtidaiyah Raudlatul Anwar is one of the private schools in the Pagedangan area. In carrying out their activities, administrative officers must record new student data into the new student registration book, the payment process and the recording of payment data reports are still manually. The design of the system made using the PHP and MYSQL programming languages for database storage. By applying the Waterfall Method is one of the SDLC models that is often used in the development of information systems or software. With the application of the student registration information system and payment of SPP this application can make it easier for officers to make reports and record new student registrations faster and stored properly.